Fibrinogen Concentrate as an Alternative to Cryoprecipitate in a Postcardiopulmonary Transfusion Algorithm in Infants Undergoing Cardiac Surgery: A Prospective Randomized Controlled Trial. (March 2020) - Downey, Laura A.; Andrews, Jennifer; Hedlin, Haley; Kamra, Komal; McKenzie, E. Dean; Hanley, Frank L.; Williams, Glyn D.; Guzzetta, Nina A.
Abstract : BACKGROUND: Infants undergoing cardiac surgery are at risk for bleeding and massive transfusion due to an immature coagulation system, complex surgeries, and cardiopulmonary bypass (CPB) effects. Hemodilution from CPB promotes an acquired hypofibrinogenemia that results in impaired fibrin formation, inadequate clot formation, and increased bleeding. In North America, the current standard of care to supplement fibrinogen is cryoprecipitate. An alternative option is the off-label use of fibrinogen concentrate (FC; RiaSTAP; CSL Behring, Marburg, Germany), a purified fibrinogen. Because perioperative allogenic transfusions are associated with increased morbidity and mortality, we sought to determine whether FC would be an acceptable alternative to cryoprecipitate in a post-CPB transfusion algorithm in infants undergoing open-heart surgery. METHODS: We randomized 60 infants (<12 months) undergoing nonemergent cardiac surgery with CPB at 2 tertiary care children's hospitals to receive either cryoprecipitate or FC in a post-CPB transfusion algorithm. Infants underwent a stratified randomization based on institution and surgical complexity. The primary outcome was the difference in number of intraoperative allogenic blood product transfusions. Secondary outcomes included 24-hour chest tube output (CTO), mechanical ventilation time, adverse events (AEs), intensive care unit (ICU) length of stay (LOS), hospital LOS, postoperative thrombosis, and death within 30 days of surgery. The primary analysis followed the intent-to-treat (ITT) principle and was performed using linear regression adjusted for institution and complexity of surgery. A per-protocol (PP) analysis was also performed. RESULTS: Between June 2016 and January 2018, we enrolled 60 patients with complete data available for 25 patients who received cryoprecipitate and 29 patients who received FC. Patients in the cryoprecipitate group (median age: 4 months [2–6 months]) received 5.5 (4.0–7.0) allogeneic blood units in the ITT analysis and 6.0 units (5.0–7.0 units) in the PP analysis. Patients in the FC group (median age: 4 months [2–5]) received 4 units (3.0–5.0 units) in the ITT analysis and 4.0 units (3.0–5.0 units) in the PP analysis. In the adjusted ITT analysis, the FC group received 1.79 units (95% confidence interval [CI], 0.64–2.93; P = .003) less than the cryoprecipitate group. In the adjusted PP analysis, the FC group received 2.67 units (95% CI, 1.75–3.59; P < .001) less than the cryoprecipitate group. There were no significant differences in secondary outcomes or AEs. CONCLUSIONS: Our findings suggest that FC may be considered as an alternative to cryoprecipitate for the treatment of hypofibrinogenemia in infants with bleeding after CPB. Although we found no significant differences between secondary outcomes or AEs, further studies are needed to assess safety.